Histopathological Changes of the Retina After Nd: YAG Laser Thrombolysis in Branch Retinal Vein Occlusion: An Experimental Study - Abdelkawi, Salwa Ahmed; Hassan, Aziza Ahmed; Ghoneim, Dina Fouad; Saif, Ahmed Tamer Sayed (Journal of Lasers in Medical Sciences, 2018)
Introduction: The efficacy of many therapeutics techniques for treatment of branch retinal vein occlusion (BRVO) has been the subject of many investigations. The aim of the present work is to evaluate the transluminal Nd: YAG laser thrombolysis as a new therapeutic approach used for treatment of BRVO in rabbits as an experimental model. Methods: Four rabbits were considered as a control (n=8 eyes); occlusion of the branch retinal veins was performed by using a dye enhancing thrombus formation in right eyes of 10 rabbits (n=10 eyes). Thrombi in the retinal veins were induced by intravenous injection of rose bengal solution as a photosensitizer immediately before the argon laser application with a power of 1200 mW, a spot size of 100 μm, and a duration of 20 ms. One week later, transluminal Nd: YAG laser thrombolysis (30 mJ, 3 pulses/4 ns) was employed to the site of occluded veins, until the thrombi were partially or completely shattered. The rabbits were followed up after 4 days, 1 week and 2 weeks for slit lamp fundus examination and the treated retinas were isolated for histopathological examination. Results: Argon laser photothrombosis induced complete BRVO with some vitreous hemorrhage, destruction, and necrosis in the surrounding retinal layers. Moreover, one week later, Nd: YAG laser thrombolysis showed complete venous flow, minimal vitreous hemorrhage, reperfused retina, complete veins improvement. Follow up after 2 weeks revealed more improvement of all retinal layers. Conclusion: Treatment with transluminal Nd: YAG laser thrombolysis represented a novel therapeutic modality in BRVO.